IMPLEMENTASI NILAI-NILAI DEMOKRASI DALAM PEMBELAJARAN SEJARAH MELALUI MODEL CTL (CONTEXTUAL TEACHING LEARNING) UNTUK MEMBANGUN SIKAP SOSIAL DAN HASIL BELAJAR SISWA KELAS XI DI SMA AL ISLAM 1 SURAKARTA TAHUN PELAJARAN 2015/2016 - Yana, Ifada Rashida; Musadad, Akhmad Arif; Pelu, Musa (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2017)
This research was aimed to build social attitude and to increase students? learning result in grade XI Social II SMA Al Islam 1 Surakarta by applying democratic value using learning model using Contextual Teaching Learning in History Learning.This study was a Class Action Research which held in two cycles. Every cycle consisted of action plan, action, observing, and reflecting. The subject of the research was 34 students of grade XII Social SMA Al Islam 1 Surakarta. Data source was from the teacher, the students, and teaching-learning process. The technique of collecting data was using test, observation, interview, and documentation. Validity test used triangulation technique, which were triangulation data and triangulation method. The analysis of the data was using descriptive comparative technique. The research model was using spiral model (planning, acting, observing, and reflecting).The result of the research showed that the researcher as the teacher might be said that she could teach well in the teaching and learning process, so it could walk properly. The teacher?s teaching ability in the cycle 1 was 72.4% increased to 93.3% in the cycle II. Students? learning result could be categorized into a good level. It could be seen by the percentage of completeness of student learning outcomes in pre-action class passing grade until 41.2% increased to 64.7%. In addition, the second cycle had been also increasing; the class passing grade was in the rank of 88.2% from 34 students or 30 students. However, to the social attitude of the students in the learning process could be categorized into a very good condition. It could be seen by the percentage of the questionnaire result of social attitude from all the students in the pre action class about 69.6% became 75.2% in the cycle I, then having increased again in cycle II about 90% from all the students in the class.Based on the result and the discussion of the research, it could be concluded that the implementation of democratic value using CTL model can build social attitude and learning result of the students grade XII Social 2 in SMA Al Islam 1 Surakarta.